Kajian Sosioreligius Barong Landung Dalam Pemujaan Sasuhunan Prawelan Bhatara Galungan Kuningan - I Nyoman Temon Astawa; Ni Komang Sudarningsih; Ni Made Rai Kristina (Jurnal Penelitian Agama Hindu, 2022)
The worship of Barong Landung as Sasuhunan Prawalen Bhatara Galungan Kuningan is an effort to create a sense of security, tranquility, peace and inner and outer prosperity in social life. Nowadays, the Barong Landung worship procession becomes a quite interesting phenomenon. The reality faced by society is that there are still many people who do not understand the essence of worshiping Barong Landung with various rituals and the uniqueness contained in it. The existence of Sasuhunan Prawalen Bhatara Galungan Kuningan is understood with various perceptions and beliefs of the community, so that in the procession of worshipers it is seen that the enthusiasm of the community, especially the youth, is scrambling to get back, nyolahang Ida Bhatara, in addition to other uniqueness. The worship of Barong Landung in Sasuhunan Prawalen Bhatara Galungan Kuningan is believed by the community as a place to ask for safety and prevent the community from mrana. The Mythology of the Worship of Barong Landung, apart from being the embodiment of Sasuhunan Prawalen Bhatara Galungan Kuningan, is also believed to be a medium to invoke healing for the illness suffered by krama. Prawalen Bhatara Galungan and Kuningan who reside in Barong Landung, apart from being the center of worship, also Ida Bhatara Ngemargiang Matetambaan or Ngemargiang Usada (treatment) is believed to be very effective in getting rid of gering mumps. Socio-Religious Hindu values ​​in worshiping Sasuhunan Prawalen Bhatara Galungan Kuningan include the value of God, the value of kinship, and the value of solidarity.